Twitter as a teaching practice to enhance active and informal learning in higher education: The case of sustainable tweets - Kassens-Noor, Eva (Active learning in higher education, 2012)
With the rise of Web 2.0, a multitude of new possibilities on how to use these online technologies for active learning has intrigued researchers. While most instructors have used Twitter for in-class discussions, this study explores the teaching practice of Twitter as an active, informal, outside-of-class learning tool. Through a comparative experiment in a small classroom setting, this study asks whether the use of Twitter aids students in learning of a particular subject matter. And if so, in which learning contexts Twitter offers advantages over more traditional teaching methods. This exploratory study showed potential opportunities and pitfalls that Twitter could bring to the e-learning community in higher education.